Monolayer Behaviors of Carborane Poly(Ethylene Glycol) Complexes. (5th February 2019) - Kim, Sunhye; Yang, Jingying; Jang, Eunsuk; Paeng, Keewook; Sohn, Daewon
Abstract : Carborane (CB), a cluster composed of boron, carbon and hydrogen atoms, has been recognized for its unique properties and potential as a boron neutron capture therapy (BNCT) material. Solubility problems of CB can be solved by connecting each CB with polyethylene glycol (PEG). PEG's having three different molecular weights (Mwt. 3800, 5010, and 6000) were connected to CB, and their Langmuir films were studied by surface pressure (Π)‐surface area (Å) isotherm, hysteresis, and atomic force microscopy (AFM). CB‐PEG complexes have different limiting areas according to the molecular weight of PEG and form a close‐packed arrangement for higher molecular weights of PEG. CB‐PEG complexes create dot domains at low pressure, and the domains aggregate to larger domains as the surface pressure is increased. With a smaller molecular weight of PEG, a more rigid and well‐ordered monolayer is obtained by interaction of the hydrophilic PEG and hydrophobic CB. Intermolecular interactions are lowered by adding salt to the subphase, which generates more reversible monolayers. Abstract :